Biological CO2 Uptake and Upwelling Regulate the Air-Sea CO2 Flux in the Changjiang Plume Under South Winds in Summer - Li, Dewang; Ni, Xiaobo; Wang, Kui; Zeng, Dingyong; Wang, Bin; Jin, Haiyan; Li, Hongliang; Zhou, Feng; Huang, Daji; Chen, Jianfang (Frontiers in Marine Science, 2021)
The partial pressure of CO2 (pCO2) in the sea and the air-sea CO2 flux in plume waters are subject to interactions among biological production, horizontal advection, and upwelling under wind events. In this study, time series of pCO2 and other biogeochemical parameters in the dynamic Changjiang plume were presented to illuminate the controlling factors of pCO2 and the air-sea CO2 flux after a strong south wind event (July 23–24, maximum of 11.2 ms–1). The surface pCO2 decreased by 310 μatm (to 184 μatm) from July 24 to 26. Low-pCO2 waters (<200 μatm) were observed in the following 2 days. Corresponding chlorophyll a and dissolved oxygen (DO) increase, and a significant relationship between DO and npCO2 indicated that biological uptake drove the pCO2 decrease. The salinity of undersaturated-CO2 waters decreased by 3.57 (from 25.03 to 21.46) within 2 days (July 27–28), suggesting the offshore advection of plume waters in which CO2 had been biologically reduced. Four days after the wind event, the upwelling of high-CO2 waters was observed, which increased the pCO2 by 428 μatm (up to 584 μatm) within 6 days. Eight days after the onset of upwelling, the surface pCO2 started to decrease (from 661 to 346 μatm within 3 days), which was probably associated with biological production. Regarding the air-sea CO2 flux, the carbon sink of the plume was enhanced as the low-pCO2 plume waters were pushed offshore under the south winds. In its initial stage, the subsequent upwelling made the surface waters act as a carbon source to the atmosphere. However, the surface waters became a carbon sink again after a week of upwelling. Such short-term air-sea carbon fluxes driven by wind have likely occurred in other dynamic coastal waters and have probably induced significant uncertainties in flux estimations.